Fibroblast response to initial attachment and proliferation on titanium and zirconium surfaces. - Araceli Meza-Rodríguez; Omar Martínez-Álvarez; Laura Acosta-Torres; Javier de la Fuente-Hernández; René García-Contreras (Universidad de Concepción., 2016)
Introduction: In recent decades, dental implants have become one of the best options for comprehensive dental restoration; their placement is a multidisciplinary task that requires a solid understanding of biological, periodontal, surgical and prosthetic principles. Objective: The aim of this study was to quantify in vitro the adhesion and proliferation of human gingival fibroblasts (HGF) response on titanium (Ti) and zirconia (Zr) surfaces. Methodology: Samples of Ti and Zr were observed under atomic force microscopy (AFM). HGFs were inoculated in each sample to determine adhesion and cell proliferation. The reagent MTT was mixed with medium DMEM and inoculated in each plate; formazan was dissolved with dimethyl sulfoxide and analyzed at 540nm in a microplate spectrophotometer. The test was performed with three independent experiments. Data were analyzed with Kolmogorov-Smirnov tests (Lilliefors), Kruskal-Wallis tests and Mann-Whitney test comparisons. Results: Topography of the Zr plates showed greater roughness (Ra=0.39μm) than Ti (Ra=0.049μm). Quantification of HGF adhesion was significantly higher (p<0.05) in Ti, while proliferation showed no statistically significant differences between the groups. Conclusion: It is noteworthy that, even though Ti initially showed increased cell adhesion on the surface, after 24h Zr samples showed similar proliferation; this demonstrates that both surfaces have a comparable biological response.